A genome-wide association study of Dupuytren's disease reveals 17 additional variants implicated in fibrosis - Ng, M; Thakkar, D; Southam, L; Werker, P; Ophoff, R; Becker, K; Nothnagel, M; Franke, A; Nurnberg, P; Espirito-Santo, A; Izadi, D; Hennies, H; et al. (Cell Press, 2017)
Individuals with Dupuytren’s disease (DD) are commonly seen by physicians and surgeons across multiple specialties. It is an increasingly common and disabling fibroproliferative disorder of the palmar fascia, which leads to flexion contractures of the digits, and is associated with other tissue specific fibroses. DD affects between 5 and 25% of people of European descent, and is the most common inherited disease of connective tissue. We undertook the largest GWAS to date in individuals with a surgically validated diagnosis of DD from the UK, with replication in British, Dutch and German individuals. We validated association at all nine previously described signals, and discovered 17 additional variants with P≤5x10-8. As a proof of principle, we demonstrated correlation of the high-risk genotype at the statistically most strongly associated variant with decreased secretion of the soluble WNT-antagonist SFRP4, in surgical specimen derived DD myofibroblasts. These results highlight important pathways involved in the pathogenesis of fibrosis, including WNT signaling, extracellular matrix modulation, and inflammation. In addition, many associated loci contain genes that are hitherto unrecognized as playing a role in fibrosis, opening up new avenues of research that may lead to novel treatments for DD and fibrosis more generally. DD represents an ideal human model disease for fibrosis research.